Capital Structure and Financial Performance of Quoted Oil and Gas Companies in Nigeria - Irene, Ehimare; Abusomwan, Rachael E.; Jackson-Akhigbe, Beauty E. (Archives of Business Research, 2025)
This study investigates the impact of capital structure on the financial performance of quoted oil and gas companies listed on the Nigerian Exchange Group. Specifically, it examines the effects of total debt ratio, long-term debt ratio, short-term debt ratio, and equity ratio on the market value of firms, measured by Tobin's Q, over the period from 2014 to 2023. The research utilizes a longitudinal approach with a sample of eight publicly traded oil and gas companies, employing data obtained from annual reports. A random effects model, analyzed through panel least squares regression, was used to assess the relationships between the financial ratios and firm performance. The results revealed that total debt ratio positively influences firm performance, indicating that higher total debt is associated with increased firm market value. Conversely, long-term and short-term debt ratios exhibit negative impacts on firm performance as measured by Tobin's Q, suggesting that excessive long-term and short-term debt can reduce market value. The equity ratio shows a significant positive relationship with Tobin's Q, implying that a higher equity ratio enhances firm performance.